2019
DOI: 10.1111/bph.14561
|View full text |Cite
|
Sign up to set email alerts
|

A novel nitroalkene‐α‐tocopherol analogue inhibits inflammation and ameliorates atherosclerosis in Apo E knockout mice

Abstract: Background and purpose Atherosclerosis is characterized by chronic low‐grade inflammation with concomitant lipid accumulation in the arterial wall. Anti‐inflammatory and anti‐atherogenic properties have been described for a novel class of endogenous nitroalkenes (nitrated‐unsaturated fatty acids), formed during inflammation and digestion/absorption processes. The lipid‐associated antioxidant α‐tocopherol is transported systemically by LDL particles including to the atheroma lesions. To capitalize on the overla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 62 publications
0
7
0
1
Order By: Relevance
“…We have previously demonstrated that a rationally designed nitroalkene derived from a natural and safe drug delivery system (e.g. α-tocopherol or Vitamin E), was a novel and thriving pharmacological strategy for the treatment of atherosclerosis [ 47 ]. This strategy, which was named NATOH (5-nitroethenyl-γ-tocopherol) and was specifically designed to be carried by the VLDL/LDL system to atheroma lesions by homologizing the α-tocopherol structure, probed to work as a non-conventional anti-inflammatory compound in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously demonstrated that a rationally designed nitroalkene derived from a natural and safe drug delivery system (e.g. α-tocopherol or Vitamin E), was a novel and thriving pharmacological strategy for the treatment of atherosclerosis [ 47 ]. This strategy, which was named NATOH (5-nitroethenyl-γ-tocopherol) and was specifically designed to be carried by the VLDL/LDL system to atheroma lesions by homologizing the α-tocopherol structure, probed to work as a non-conventional anti-inflammatory compound in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…This strategy, which was named NATOH (5-nitroethenyl-γ-tocopherol) and was specifically designed to be carried by the VLDL/LDL system to atheroma lesions by homologizing the α-tocopherol structure, probed to work as a non-conventional anti-inflammatory compound in vitro and in vivo . Moreover, NATOH was able to decrease the atherosclerotic plaque formation and to inhibit the expression of relevant cytokines and adhesion molecules liberated at the lesions site in an atherosclerosis mouse model (ApoE knock out mice) [ 47 ]. In this work, we show that a novel and hydro soluble derivative of NATOH, named NATx0, previously described by our group [ 48 ], has promissory beneficial effects over inflammatory processes occurring during obesity, glucose intolerance and type II diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endogenous electrophilic nitroalkene fatty acids are known to target different signaling pathways including Nrf2 and NF-κB [18][19][20]. Recently, we reported the synthesis, physicochemical characterization, and therapeutic effects of nitroalkene-tocopherol analog compounds [21,22], laying the foundation for the rational design of novel nonconventional anti-inflammatory compounds. The addition of an electrophilic nitroalkene moiety to the tocopherol scaffold confers the hybrid compound with multifaceted therapeutical activity in a model of atherosclerosis through combined inhibition of NF-κB signaling and activation of Nrf2-Keap1 [22].…”
Section: Introductionmentioning
confidence: 99%
“…Esses processos são intimamente relacionados aos mecanismos fisiopatológicos da formação de ateromas e ateroscleroses. 3 Nesse contexto, a Bryophyllum pinnatum (Lam.) Oken (sinônimo: Kalanchoe pinnata (Lam.…”
Section: Introductionunclassified